An international survey of applied face-matching training courses. (October 2021) - Moreton, Reuben; Havard, Catriona; Strathie, Ailsa; Pike, Graham
Highlights: Facial examiners training is longer and more detailed than facial reviewer training. The content, delivery and duration of training varies between agencies. One-to-one mentoring is commonly used in face-matching training. Low adoption of evidence-based training practices. Abstract: Face matching decisions in applied settings are typically carried out by trained face-matching professionals, known as facial reviewers and facial examiners. Recent research has demonstrated that short professional face-matching training courses are limited in improving face-matching accuracy, however, despite the existence of high-level training guidelines produced by the practitioner community the content, duration and delivery of training for facial reviewers and facial examiners are not widely understood in the academic research community. The current study aimed to address this gap in the scientific literature to better understand how different agencies train facial reviewers and facial examiners, using results collected from an international survey. The survey included questions on the duration, delivery and content of an agencies face-matching training. 24 face-matching agencies from five continents took part in the survey. A quantitative analysis of the survey results revealed that at the group level facial examiners received longer durations of training, covering more topics than reviewers and more frequently included one-to-one mentoring. However, the survey revealed large differences in the duration, delivery methods and content of training by individual agencies at both the facial review and facial examiner level and low inclusion of evidence-based training practices. These results should help researchers to better understand the diversity in training practices and durations of training between different agencies and may help explain the individual differences observed in the performance of face matching professionals in the literature.